How Should the Paradigm of Islamic Economic Research Be Understood? - Sjafruddin, Sjafruddin; Zainuri, Hamzah (Prodi Hukum Ekonomi Syariah STAIN Teungku Dirundeng Meulaboh, 2025)
Islamic economics is still a relatively new field within academic discourse, especially when compared to other more established branches of Islamic sciences. The practice of Islamic economics in the market has spurred further investigation and research to address the emerging challenges and issues. A key problem that arises is the dominance of quantitative-positivistic approaches, which have come to be regarded as